Uranyl Speciation in the Presence of Specific Ion Gradients at the Electrolyte/Organic Interface. Issue 1 (2nd January 2022) - Kumar, Nitesh; Servis, Michael J.; Clark, Aurora E.
ABSTRACT: Uranyl (UO   2 2 + ) speciation at the liquid/liquid interface is an essential aspect of the mechanism that underlies its extraction as part of spent nuclear fuel reprocessing schemes and environmental remediation of contaminated legacy waste sites. Of particular importance is a detailed perspective of how changing ion concentrations at the liquid interface alter the distribution of hydrated uranyl ion and its interactions with complexing electrolyte counterions relative to the bulk aqueous solution. In this work, classical molecular dynamics simulations have examined uranyl in bulk LiNO   3 ( a q ) and in the presence of a hexane interface. UO   2 2 + is observed to have both direct coordination with NO   3 − and outer-sphere interactions via solvent-separated ion-pairing (SSIP), whereas the interaction of Li   + with NO   3 − (if it occurs) is predominantly as a contact ion-pair (CIP). The variability of uranyl interactions with nitrate is hypothesized to prevent dehydration of uranyl at the interface, and as such the cation concentration is unperturbed in the interfacial region. However, Li   + loses waters of solvation when it is present in the interfacial region, an unfavorable process that causes a Li   + depletion region. Although significant perturbations to ion–ion interactions, solvation, and solvation dynamics are observed in the interfacial region, importantly, this does not change the association constants of uranyl with nitrate. Thus, the experimental association constants, in combination with knowledge of the interfacial ion concentrations, can be used to predict the distribution of interfacial uranyl nitrate complexes. The enhanced concentration of uranyl dinitrate at the interface, caused by excess adsorbed NO   3 −, is highly relevant to extractant ligand design principles as such nitrate complexes that are the reactants in ligand complexation and extraction events.